(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement The Opioid Awareness and Support Team (OAST) at the Memorial University Faculty of Medicine is a novel student-led initiative designed to supplement medical student learning related to opioid use disorder and the opioids crisis. OAST has focused on grounding educational initiatives related to opioid use disorder in the local community context, working with community partners, and bringing in individuals with lived experience. We present initial findings from an Opioid Education Day that suggest student-led supplemental education for medical students can improve student knowledge surrounding opioid use.